Komunikasi Keluarga Sebagai Upaya Pencegahan Kasus Judi Online (Studi Kasus Remaja Desa Lalibo Kecamatan Mawasangka Tengah) - Iksan, Evi Elfina; Hidayatullah, Muh.; maulana, Harry fajar (CV. ITTC INDONESIA, 2025)
The phenomenon of online gambling is increasingly worrying, especially among teenagers, which can contribute to increased crime rates and other social problems. In Lalibo Village, Central Mawasangka Sub-district, there has been a significant spike in the number of teenagers involved in online gambling activities. This problem is influenced by various factors such as economic pressure, social environment, uncontrolled access to technology, as well as low digital literacy and supervision from parents. This research aims to deeply understand the factors that drive teenagers' involvement in online gambling and explore the communication challenges between teenagers and parents in tackling this phenomenon. The research method used is descriptive with a qualitative approach. Data collection was conducted through participatory observation, in-depth interviews with teenagers, parents, community leaders, and village officials, and literature study. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results showed a sharp contrast between teenagers' and parents' perceptions of online gambling. Teenagers tend to view online gambling as entertainment and a quick way to earn money, while parents consider it a serious threat to their children's moral and financial development. Family communication patterns in discussing online gambling are still limited, due to parents' lack of knowledge about the digital world, a sense of intimacy, and a lack of knowledge about online gambling.